DESCRIPTION OF COMMUNITY KNOWLEDGE AND ATTITUDES ABOUT FIRST AID IN TRAFFIC ACCIDENTS - Romalina, Romalina; Widya Jannatul Amani; Elsa Gusrianti; Daniati, Meisa (Bajang Institute, 2024)
A traffic accident is an unexpected and unintentional road event involving a vehicle with or without other road users that results in human casualties and property damage (UU RI, 2009). The World Health Organization (2018) states that traffic accidents are ranked eighth as a cause of death in the world with 1.35 million victims dying each year. This study aims to see a picture of community knowledge and attitudes about first aid in traffic accidents in Riau Islands Province in 2022. This type of research is quantitative and the research design used is descriptive with retrospective data collection. The population of this study was 32 people. The sampling technique used was accidental sampling. In this study, it is known that the majority of people have high knowledge with 29 respondents (91%) and show a moderate attitude with 27 respondents (84%). This is influenced by several factors, namely education, sources of information, and experience. The results of this study are expected for the community to be able to increase knowledge about and attitudes about first aid in traffic accidents by attending training and education, so that they can participate in first aid efforts for victims of traffic accidents.